Building cost management systems for quality assurance at Russian defense enterprises - A. S. Baldina (Омский научный вестник)
The article examines the issues of system management of quality assurance costs at Russian defense enterprises. The relevance of the work is determined by the increased requirements for saving resources that are currently imposed on enterprises of the military-industrial complex. The purpose of the work is to develop recommendations for building a quality cost management system at Russian defense enterprises based on a process approach. This work is based on the results of research by Russian and foreign scientists in the field of quality cost management, reflected in scientific articles, monographs, textbooks. In addition, publications of practitioners in the field of quality management in industry journals and on specialized Internet portals were used. The author offers a generalized model of the system of formation of costs for ensuring the quality of products. When managing quality costs, it is proposed to initially start from the prices of the designed products. On their basis, the optimal (taking into account existing conditions) production cost of products is calculated. Cost data is used as a guideline for R&D. Special attention is paid to the formation of responsibility centers in the quality cost management system.